(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Surgical site infection (SSI) is most common type of Hospital Acquired Infection (HAI) in low and middle-income countries. The objective of the study was to find out the incidence and associated factors of SSI following obstetric surgeries especially Lower Segment Cesarean Section (LSCS). MATERIALS AND METHODS: A retrospective cross sectional study was conducted at Chitwan Medical College Teaching Hospital. A total of 1739 patients files who had undergone Lower Segment Cesarean Section from 14th April 2019 to 12 April 2020 was reviewed. Data was analysed using IBM SPSS Version 20.0 and interpreted in descriptive and inferential statistics. RESULTS: Among 1739 obstetric surgeries performed, 50 patient showed signs and symptoms of SSI yielding to an infection rate of 2.9%. Majority (80%) of patients developed SSI after they were discharged. There was significant association between SSI and type of surgery (p=0.007) and, SSI was not associated with haemoglobin level, blood transfusion, residence and age of the patients. CONCLUSIONS: Though overall infection rate was low, most of the women developed infection after being discharged, thus it is recommended that discharge counselling about wound care should be emphasized.